2016
DOI: 10.1002/nau.23167
|View full text |Cite
|
Sign up to set email alerts
|

Vesicovaginal fistulas in the developed world: An analysis of disease characteristics, treatments, and complications of surgical repair using the ACS‐NSQIP database

Abstract: In the US VVF remains a rare entity. Over half of VVFs were repaired vaginally. The occurrence of serious complications is low. A vaginal approach appears to be associated with fewer complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 8 publications
4
16
0
1
Order By: Relevance
“…8,9 Previous studies have demonstrated higher rate of complications associated with an abdominal approach, including urinary tract infections, sepsis, blood transfusions, and hospital readmissions. 6,7 Results from our study are consistent with published data advocating for vaginal approach in regards to risk of perioperative blood transfusion as well. However, there are circumstances in which an abdominal approach may be indicated, such as for ureteric involvement, limited vaginal access, significant associated scarring or failed prior repairs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…8,9 Previous studies have demonstrated higher rate of complications associated with an abdominal approach, including urinary tract infections, sepsis, blood transfusions, and hospital readmissions. 6,7 Results from our study are consistent with published data advocating for vaginal approach in regards to risk of perioperative blood transfusion as well. However, there are circumstances in which an abdominal approach may be indicated, such as for ureteric involvement, limited vaginal access, significant associated scarring or failed prior repairs.…”
Section: Discussionsupporting
confidence: 91%
“…A rare complication of fistula surgery is hemorrhaging, accounting for 3% of all complications. 6 However, this can be serious and life-threating as access to safe blood for women in low-resource settings can be challenging. Therefore, it is important to understand potential risk factors for perioperative transfusions to allow for proper planning and risk mitigation among high-risk women.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear if the cost to society, and a national healthcare system such as that in the UK, would be different for each of the techniques. However, the increased length of stay and morbidity associated with an open abdominal approach as reported elsewhere would suggest that the societal cost of a successful abdominal repair might be likely to be greater than that of a vaginal repair [12].…”
Section: Success Ratementioning
confidence: 87%
“…In a bid to provide assistance in making this decision, our series demonstrates an evolution in practice for a single surgeon from a predominantly abdominal approach to a predominantly vaginal approach. This progression was made in a bid to reduce the exposure of patients to the greater morbidity seen with an abdominal approach, as identified by previous studies [12].…”
Section: Surgical Approachmentioning
confidence: 99%
“…The most common cause of VVF in developed countries is pelvic surgery e.g. hysterectomy while in developing countries prolonged obstructed labour is the leading cause 11 . Contrary to various studies from Pakistan, we found hysterectomy as the most common cause.…”
Section: Discussionmentioning
confidence: 99%